TANGGAPAN MAHASISWA TERHADAP KUALITAS PELAYANAN DITINJAU DARI KEPENTINGAN (IMPORTANCE) DAN KINERJA (PERFORMANCE) PADA FAKULTAS ILMU KESEHATAN UNIVERSITAS IBN KHALDUN BOGOR . - Suharti, Titing (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2013)
Research was carried out to examine how student’s perception about ” Faculty of Health University of Ibn Khaldun Bogor service quality related with importance and performance,” and also to find indicators of service quality must be considered by faculty.The research method applied in this study is survey. Samples took from population has been fixed. Questionnaire was to collect data. There were 30 repondent selected from 136 students. Data would be analyzed with descriptive statistics, whereas to know students perception about facultys performence, researcher applied importance- performance analysis.The results of study showed important indicators which costumers believe in, they were indicators off office facilities and infrasructures, indicators of how fast staff could overcome students problems, and indicator of assurance of fund availability.